The economics of Kentucky coal - Harvey, Curtis E. (The University Press of Kentucky, 1977)
The energy problem confronting the United States has focused attention on Kentucky's coal. Mr. Harvey here presents a comprehensive analysis of the coal industry in Kentucky, which consistently produces more than a fifth of the nation's coal. Because the coal industries in eastern and western Kentucky differ in many respects, Mr. Harvey has analyzed them separately. Although faced with competition from the foreign oil market, prospects for eastern Kentucky coal seem favorable because of its high quality and easy access to markets. The future of the coal industry in western Kentucky, Mr. Harvey.